Characterization of natural and synthetic casings and mechanism of BaP penetration in smoked meat products. (May 2015) - Ledesma, Estefanía; Rendueles, Manuel; Díaz, Mario
Abstract: Meat product casings are able to prevent the penetration of chemical and potentially carcinogenic compounds. Some components play an important role in the food safety of smoked meat products. In this study, the penetration of benzo(a)pyrene (BaP) (a polycyclic aromatic hydrocarbon [PAH] marker) in smoked meat products stuffed in different casings (natural and synthetic) has been tested. It was found that, in contrast to natural casing, collagen casing prevents BaP contamination of smoked meat products. The reasons of this fact have never been explained. Porosimetry and physical morphology determination by means of scanning electron microscope (SEM) and Fluorescence Stereo Microscope images of both types of unsmoked and smoked casings and different depths of 48 chorizos stuffed with both casings subjected to 0–10 days of smoking were studied to explain this effect. Based on the results, a mechanism can be inferred to explain BaP penetration inside the products. During smoking, meat products are heated and dried. The wrinkled morphology and high porosity (66.8%) of natural casing makes the fat flows outward through the casing making its surface sticky. Soot particles and tar aerosols containing polycyclic aromatic hydrocarbons (PAH) stick to this surface and then start to migrate inwards. In contrast, the smooth morphology and low porosity (16.6%) of synthetic casing make it a barrier, impeding the fat from exiting the inside of the casing. In this case, the product shows a hard, dry external surface with less affinity for soot particles, whose possibility of penetrating the product is hindered by the small pore size of the casing. Highlights: BaP penetration in smoked meat products stuffed with different casings was studied. Collagen casing prevents BaP contamination of smoked meat products. Porosity and morphology of casings and 48 chorizos smoked 0–10 days were tested. Wrinkled morphology and high porosity of natural casings (66.84%) lead to BaP contamination. Smooth surface and low porosity of collagen casings (16.63%) prevent BaP contamination.